Is One Page Lesson Plan Better?: Voices of English Teachers - Ni Kadek Nita Rahayu; I.G.A. Lokita Purnamika Utami; Ida Ayu Made Istri Utami (Universitas Pendidikan Mandalika, 2021)
Lesson plan is an essential part in teaching and learning process. Recently, the government was released the Circular Letter number 14 of 2019 regarding to the simplification of lesson plan. It announced that one-page lesson plan as the new lesson plan format used in Indonesia. The one-page lesson plan format is shorter than the previous lesson plan, where the teachers only required to fulfill 3 main components and the other components are belonging to non-compulsory components. One-page lesson plan has three principles, namely effective, efficient, and student-oriented. This study aims at analyzing the English teachers' perspectives toward the one-page lesson plan principles at SMKN 3 Singaraja. The study was designed with a case study qualitative approach. The data were gathered by conducting an in-depth interview with the teachers. The study was involved four English teachers at SMKN 3 Singaraja. This study shows all of the English teachers have the same perspectives on one-page lesson plan principles that one-page lesson plan is more effective, efficient, and student-oriented if compared to the previous lesson plan format. The findings of this study imply that one-page lesson plan format helps the teachers easier to design an efficient, effective and more student-oriented instruction.